Translating knowledge into practice for communication skills training for health care professionals. Issue 11 (November 2022) - Ammentorp, Jette; Chiswell, Meg; Martin, Peter
Abstract: Despite the evidence that person-centred communication underpins all that we do in our interactions with patients, caregivers and team members, the knowledge about the implementation of systematic communication skills training is still in its infancy. This position paper describes some of the main contextual facilitators for translating knowledge about communication skills training for health care professionals (HCP) and recommends ways to guide practical implementation. Based on the literature that has been published over the last two decades, it seems evident that communication skills training programs should be underpinned by clinician self-reflection, be experiential, and focused on behaviour change and implementation of new skills into practice. The programs should be delivered by trainers possessing an understanding of communication micro skills, the skills and confidence to observe interactions, and coach learners through the rehearsal of alternative approaches. Communication skills programs should be flexible to adapt to individual learners, local needs, and circumstances. Interventions should not be limited to the empowerment of individual HCP but should be a part of the organisational quality assurance framework, e.g., by including communication skills in clinical audits. Implementation science frameworks may provide tools to align programs to the context and to address the determinants important for a sustained implementation process. Programs need to be embedded as 'core business', otherwise the culture change will be elusive and sustainability under threat if they are only dependent on provisional funding.